Integrating Humanist Values in Religious-Based Education: A Strategic Approach in Madrasahs - Ake Prasong, Mutia (Early Publishing, 2025)
This research aims to explore and analyze humanist religious-based education strategies. This strategy integrates universal human values with the principles of specific religions, focusing on the holistic development of individual potential, including cognitive, affective, and spiritual aspects. This study will examine how a humanist approach within the context of religious education can enhance students' understanding of inclusive religious values, tolerance, empathy, and social responsibility. Furthermore, this research will also identify the challenges and opportunities in the implementation of humanist religious-based education strategies in various educational contexts. The research methods used may include literature studies, document analysis, interviews with education practitioners and religious leaders, and observations of educational practices. Based on the research, it was found: (1) The concept of humanist and religious education is based on five basic principles; (2) At Madrasa, the religious humanist education strategy is implemented through a learning process that fosters values, provides students with a variety of experiences, and creates a supportive environment. (3) The religious humanist education strategy at Madrasa is carried out by strengthening the vision of Madrasa.